1995
DOI: 10.1159/000147756
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Incipient Mesoderm Formation in the Rabbit Embryo: A Light- and Retrospective Electron-Microscopic Study

Abstract: Mesoderm formation is a hallmark of vertebrate gastrulation and, at the same time, one of the prime examples for epithelio-mesenchymal transformation. Recent advances in experimental embryology and molecular biology have clarified the role of growth factors and genes in this process; however, its microscopic anatomy in higher vertebrates is still far from clear. Therefore, the present study describes the morphology of mesoderm formation in the rabbit embryo, a species which may be representative for both the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 10 publications
(16 reference statements)
2
37
0
Order By: Relevance
“…16 To maintain epithelial integrity, epiblast cells may vault over ingressing mesoderm cells as has been described in rabbits. 17 Bottle shaped cells progressively lose their contact with the apical surface as finger-like projections of surrounding epiblast cells bridge over the ingressing cell and meet apically enclosing the ingressing cell. Therefore when an ingressing cell breaks down its adherens junctions to neighboring epiblast cells, epithelial continuity is maintained as cells remaining in the epithelium seal the gap by establishing new adherens junctions.…”
Section: Emt During Mouse Gastrulationmentioning
confidence: 99%
See 1 more Smart Citation
“…16 To maintain epithelial integrity, epiblast cells may vault over ingressing mesoderm cells as has been described in rabbits. 17 Bottle shaped cells progressively lose their contact with the apical surface as finger-like projections of surrounding epiblast cells bridge over the ingressing cell and meet apically enclosing the ingressing cell. Therefore when an ingressing cell breaks down its adherens junctions to neighboring epiblast cells, epithelial continuity is maintained as cells remaining in the epithelium seal the gap by establishing new adherens junctions.…”
Section: Emt During Mouse Gastrulationmentioning
confidence: 99%
“…16 Little is known about the mechanisms causing the disintegration of the basement membrane in the mouse primitive streak. However, studies in the rabbit show endocytotic pits with basal material in ingressing mesodermal cells suggesting that endocytosis may be involved, 17 while in vitro studies in carcinoma cells have demonstrated the activation of different metalloproteases by where epithelial cells undergo EMT, become motile, and migrate en masse to re-epithelialize after internalization. 7 Nonetheless, all ingression events occur by EMT, for example the ingression of primary mesenchyme in sea urchins 8 or the ingression of mesoderm through the subduction zones in the urodele.…”
Section: Introductionmentioning
confidence: 99%
“…Breakdown of the BM is an important event for EMT during gastrulation (Viebahn et al 1995). Recent work had shown that the BM prevents EMT and precocious differentiation of epiblast into mesoderm (Fujiwara et al 2007).…”
Section: Bm Breakdown In Flrt3 −/− Embryos Induces Emt and Mesodermalmentioning
confidence: 99%
“…Because of their shape, these cells are often described as flask or bottle cells (Rhumbler, 1899;Rhumbler, 1902;Ruffini, 1925). Apical constriction has been suggested to play a role in morphogenetic movements in a wide range of organisms, including gastrulation in shrimp (Hertzler and Clark, 1992), fly (Young et al, 1991), jellyfish (Byrum, 2001), sea urchin (Kimberly and Hardin, 1998), white sturgeon (Bolker, 1993), rabbit (Viebahn et al, 1995) and frog (Keller, 1981;Hardin and Keller, 1988), as well as in primitive streak formation in chick and rat embryos (Solursh and Revel, 1978), and neurulation in frogs (Jacobson et al, 1986). Whether apical constriction actually drives shape changes in cell sheets has been directly tested in Xenopus, sea urchin and Drosophila gastrulation.…”
Section: Cell Contraction In Morphogenesismentioning
confidence: 99%